Teachers’ Social Recognition and Self-Esteem: A Perceived Perspective of the Punjab Secondary School Teachers (Journal of Social Sciences Review, 2022)
The study under the purpose was planned to examine the relationship of secondary level teachers’ social recognition with their self-esteem. The study was descriptive and correlational by its nature as it aimed to render the perceptions of participants and correlation of variables. A multi-stage random sampling technique was adopted to pick the sample of study from population of secondary school teachers of the Punjab. At first stage four districts were selected randomly and at second stage 80 schools were selected and then five teachers from each selected schools were selected to make the total sample (N = 400) secondary school teachers. The data were collected from the selected secondary school teachers by using two questionnaires. The data were analyzed by applying statistical techniques as a mean score, independent sample t-test, Pearson “r” and One-way ANOVA, and post hoc tests to draw the results. It was concluded that there was weak and insignificant relationship existed between teachers’ self-esteem and social recognition. So, it is recommended that there should be psychological practices of social recognition to associate with their self-esteem and needed to conduct research in Pakistani context.
Keywords: Teachers’ Social Recognition; Self-Esteem; Secondary School Teachers